A 100 GHz transformer-based varactor-less VCO with 11.2% tuning range in 65nm CMOS technology - Yi, Xiang (2013)
A 100 GHz transformer-based VCO is implemented in a 65nm CMOS technology. The large and linear magnetic tuning is realized by using a triple-coupled transformer. The tuning range of the proposed VCO is from 95.37 GHz to 106.68 GHz, which is currently the widest at the frequency around and above 100 GHz in CMOS technology. The measured phase noise is -104.5 dBc/Hz @ 10 MHz offset from a carrier frequency of 100.03 GHz. The power consumption is from 3.52 to 11.9 mW across the tuning range, with a 0.8 V supply voltage. The figure-of-merit FOM is -175.5 dBc/Hz and FOMT is -176.5 dBc/Hz respectively.